Efficient Water Splitting Cascade Photoanodes with Ligand‐Engineered MnO Cocatalysts. Issue 10 (6th August 2018) - Lee, Mi Gyoung; Jin, Kyoungsuk; Kwon, Ki Chang; Sohn, Woonbae; Park, Hoonkee; Choi, Kyoung Soon; Go, Yoo Kyung; Seo, Hongmin; Hong, Jung Sug; Nam, Ki Tae; Jang, Ho Won
Abstract: The band edge positions of semiconductors determine functionality in solar water splitting. While ligand exchange is known to enable modification of the band structure, its crucial role in water splitting efficiency is not yet fully understood. Here, ligand‐engineered manganese oxide cocatalyst nanoparticles (MnO NPs) on bismuth vanadate (BiVO4 ) anodes are first demonstrated, and a remarkably enhanced photocurrent density of 6.25 mA cm −2 is achieved. It is close to 85% of the theoretical photocurrent density (≈7.5 mA cm −2 ) of BiVO4 . Improved photoactivity is closely related to the substantial shifts in band edge energies that originate from both the induced dipole at the ligand/MnO interface and the intrinsic dipole of the ligand. Combined spectroscopic analysis and electrochemical study reveal the clear relationship between the surface modification and the band edge positions for water oxidation. The proposed concept has considerable potential to explore new, efficient solar water splitting systems. Abstract : Structural formulas of Ca–ethylenediaminetetraacetic acid and BF4 ‐treated MnO/BiVO4 photoanodes show the hole transfer from BiVO4 to MnO and consequent photo‐electrochemical water splitting efficiency.